Biomechanical Strength of a Novel Tendon Splicing Open Book Technique Compared to the Pulvertaft Method Using Unembalmed Human Cadaveric Tissue. Issue 2 (May 2023) - McKee, Desirae; Wait, Eric; Lierly, Micah; Ghosh, Niloy; Sizer, Phillip S.; Cox, Cameron; Gilbert, Kerry K.
Background: Extensor pollicis longus (EPL) tendon rupture is a known complication of distal radius fractures. The Pulvertaft graft technique is currently used for tendon transfer of extensor indicis proprious (EIP) to EPL. This technique can produce unwanted tissue bulkiness and cosmetic concerns as well as hinder tendon gliding. A novel "open book" technique has been proposed, but relevant biomechanical data are limited. We designed a study to examine the biomechanical behaviours of the "open book" versus Pulvertaft techniques.Methods: Twenty matched forearm-wrist-hand samples were harvested from 10 fresh frozen cadavers (2 female, 8 male) with a mean age of 61.7 (±19.25) years. The EIP was transferred to EPL using the Pulvertaft versus "open book" techniques for each matched pair (sides randomly assigned). The repaired tendon segments were mechanically loaded using a Materials Testing System to examine graft biomechanical behaviours.Results: Mann-Whitney U test outcomes demonstrated that there was no significant difference between "open book" versus Pulvertaft techniques for peak load, load at yield, elongation at yield, or repair width. The "open book" technique demonstrated a significantly lower elongation at peak load and repair thickness, as well as significantly higher stiffness when compared with the Pulvertaft technique.Conclusions: Our findings support the use of the "open book" technique, producing comparable biomechanical behaviours compared to the Pulvertaft technique. Incorporating the "open book" technique potentially requires smaller repair volume, producing size and appearance that is more anatomic when compared with the Pulvertaft.